1,2-bis(di-tert-butylphosphino)imidazole (dtbpi): a versatile imidazole-based, rigid, bulky bisphosphine ligand for transition metals - Brill, Marcel; Rominger, Frank; Hofmann, Peter (Organometallics, 2015)
A bulky bisphosphine, 1,2-bis(di-tert-butylphosphino)imidazole (dtbpi), featuring a rigid imidazole backbone, was synthesized in a simple two-step procedure. The ligand’s coordination chemistry and electron-donating abilities were investigated in the complexes (dtbpi)Ni(FDN) (3) and [(dtbpi)Rh(CO)2]BF4 (4). Protonation of 4 at the ligand backbone’s nitrogen with strong Brønsted acids such as HBF4 and HBArF gave the dicationic dicarbonyl complexes [(H-dtbpi+)Rh(CO)2](BF4)(BArF) (5a) and [(H-dtbpi+)Rh(CO)2](BF4)2 (5b), which served as model complexes of the ligand’s imidazolium-phosphine form and permitted characterization of its donating character. In order to evaluate solely the different electronic characters of the two isosteric P donors, the complexes (dtbpi)PdCl(Me) (6) and [(dtbpi)RhCl]2 (7) were synthesized. An unexpected rearrangement of one of the formed stereoisomers of 6, with cleavage of an N-P bond, was found. A novel phosphine-phosphonium ylide ligand (8) has been made accessible via chemoselective alkylation of the carbon-bound P donor of dtbpi to yield the phosphonium salt [P-CH3-dtbpi]BF4 (2). The ylide 8 was generated in situ by deprotonation of 2 with KHMDS. Its coordination to the PdCl(Me) fragment led to the isolation of exclusively the Z isomer of [(8)PdCl(Me)] (Z-9). X-ray structure analysis of [(dtbpi)Rh(NBD)]BF4 (10) and its dicationic analogue [(H-dtbpi+)Rh(NBD)](BF4)(BArF) (11) revealed the structural changes provoked upon ligand backbone protonation.
Gesehen am 28.05.2020